(untitled) ("Conference on Universal Science Research 2023", 2023)
This scientific article discusses alternative fuels and their use. Their impact on human health is described, and how harmful they are to the environment in use. There is also some comparison of alternative fuels, their disadvantages and advantages, as well as their environmental friendliness.